THE FLEXURAL STRENGTH AND RIGIDITY OF ALBASIA NAIL-LAMINATED BEAM - J.A. Tjondro; H. Budianto; W. Aryakusuma (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2011)
The horizontally and vertically nail-laminated beams were tested in this experimental study. Twelve specimens of horizontally nail-laminated beam with the same cross section and variation of four nail spacings were tested. Nine specimens of vertically nail-laminated beam with the same nail spacing and three variations of cross sections, namely rectangular, I and box also were investigated. The hardwood fast growing species, Albasia (Albizia Falcata) was used. All specimens were made from four Albasia wood planks with approximately has the same cross section area. The flexural strength, rigidity and ductility of beams were investigated. The vertically nail-laminated beam has greater strength and rigidity than horizontally nail-laminated beam, but less in ductility.